The Impact of Soil-Applied Biochars From Different Vegetal Feedstocks on Durum Wheat Plant Performance and Rhizospheric Bacterial Microbiota in Low Metal-Contaminated Soil - Latini, Arianna; Bacci, Giovanni; Teodoro, Manuel; Gattia, Daniele Mirabile; Bevivino, Annamaria; Trakal, Lukáš (Frontiers in Microbiology, 2019)
Biochar shapes soil environment and plant growth. Nevertheless, the mechanisms associated with improved plant biomass and soil microbioma in low metal contaminated soils are still unclear. In this study, the influence of biochar on soil physico-chemical properties, plant performance, and rhizosphere microbiota in durum wheat was investigated at the above- and belowground levels. Two kinds of biochar from different feedstocks (wood chips and wheat straw pellets) and two Italian durum wheat varieties, named Duilio and Marco Aurelio, were analyzed in greenhouse using a low nutrient gleyic fluvisol containing a very little amount of Pb and Zn. Four different treatments were performed: only soil control (C), soil amended with woody biochar equilibrated with nutrient solution (B1+) and non-activated (B1-), and soil amended with wheat straw biochar non-activated (B2-). Seven weeks after seed germination, 1) physico-chemical properties of soil, biochars and mixtures were assessed; 2) fresh and dry weight of aboveground plant tissues and roots, and other morphometric traits, were measured; and 3) metabarcoding of 16S rRNA bacterial gene was performed on rhizosphere soil samples. As result, the biochar from wheat straw had the stronger impact on both durum varieties, with higher electrical conductivity, higher levels of available K and Na, and a substantial increase of dissolved Na+, K+ and Cl- ions in pore water. Generally, biochar amendment decreased Zn availability for the plants. In addition, biochar improved plant growth at early growth stage and the more positive effect was achieved by combining wheat straw biochar with Marco Aurelio. Rhizosphere bacterial microbiota showed variation in alpha diversity only due to treatment; on the other side, the differential analysis showed consistent variation among samples with significant effects on amplicon sequence variant (ASV) abundance due to the specific biochar treatment as well as to the genotype. The pure B1-, for its scarce nutrient content with respect to the richer ones (B1+ and B2-), had a negative impact on microbiota richness. Our study highlight that the appropriate combination of biochar feedstock and crop species may lead to superior yield.